Factors Determining the Effectiveness of Sharia Bank Marketing Management During the Covid 19 Pandemic in Gorontalo Province - Wolok, Tineke; Kango, Umin (AIBPM Publisher, 2021)
The Covid-19 pandemic brings a significant impact on the revenue of the banking industry in addition to new challenges and risks. The micro, small and medium enterprise sector feels its great effects as the pandemic affects the ability of Islamic banks to obtain deposits from them and the level of demand for financing for productive business investments through Islamic banks. This study analyzes various determining of the effectiveness of Islamic banking marketing management in Gorontalo Province. This paper applied a qualitative method with a descriptive-analytical approach, verification, and exploratory by collecting the primary data from unstructured interviews to information sources (key informants and informants). The data was analyzed by a qualitative descriptive model in the form of data collection, data reduction, data display, and conclusions. Besides, to deepen the results of the study, a Focus Group Discussion (FGD) was conducted with all relevant competent stakeholders. The results of the study are expected to be used by local governments and Islamic banking actors in Gorontalo Province.